FAULT SEALS CHARACTERISATION THROUGH STATIC, DYNAMIC, AND GEOMECHANICAL PARAMETER, SOUTH MAHAKAM AREA, KUTAI BASIN, INDONESIA - ARIA AMAR (NIM: 22015311), RIZA
South Mahakam is an offshore area located in Kutai Basin. The area consist of three gas fields which controlled by a single strike-slip fault in Northwest-Southeast direction, called Sepinggan Fault. Jempang-Metulang, Mandu, and Stupa field are then separated by North-South normal faults that curved out in en-echelon style from the main fault as consequence of its right lateral movement. Those normal faults also play role in creating compartementalization within the field it self. The hydrocarbon zones produced by the fields is Sequence Deltaic Sepinggan, which spreads from delta-plain to pro-delta environment. Distributary channels and bars are the main reservoirs in Jempang-Metulang and Mandu, while mouth-bars pro-distals dominates the Stupa field. In term of pressure regime, hydrostatic pressure are commonly found in proximal area. This pressure increases progressively to a highly overpressured at Stupa’s area. The objective of the study is to analyze the sealing nature of the normal faults, focussed in Sepinggan Deltaic Sequences. It is suspected that fasies is the main factor that controlling the sealing nature. Thus, the goal of the study is to prove the effectiveness of the fasies in this context. The result of this study is expected to contribute in the the decision process, justifying the future development in the area either for the productive fields or for several prospects nearby. The sealing nature of the fault is analyzed through static, dynamic, and geomechanic parameters. Juxtaposition, volume of the shale (Vshale), fault’s throw, and Shale Gouge Ratio (SGR) are the main static parameter. The SGR have been chosen as shale smears algorithm, because it is considered as the most applicable algorithm for a mixed clastic sequence, as Sepinggan Deltaic Sequence. The dynamic analysis focussing on the fluid and pressure aspects, and used as the calibration’s elements of the SGR. Finally, geomechanical analysis is performed in order to understand the risk of fault’s leak based on the present tectonic regime in the area. Slip and Dilatation tendency are used as the main parameter on this subject. This study use three main approaches in claiming its objectives, which are the log, grid, and analogical approach. The calculation obtained from log data shows consistent result with the one calculated from grid data. It proves that conclusion obtained from log data is applicable for the grid, and vice versa. This consistency also justifying the analogical approach for fault that does not have enough data, by comparing the similarity of the fault’s characteristics. At the end of the study, all those logical steps can give strong conclusion, which applicable for the whole South Mahakam. Juxtaposition analysis shows that shale-shale and sand-shale juxtapose highly dominates in all faults. The average value of SGR is also known to be high as 0.63 to 0.72. This high value of SGR is not common compare to the known publications, which in the range of 0.2 to 0.4. The calculated fault’s permeability has very low value between 0.001 to 0.02 mD, and these values are below the minimum the requirement for a rock to be able to transmit the fluid. Dynamic analysis that have been performed also shows different fault’s character, between the capability to hold the differential pressure that occurs on the fault’s plane and to hold the hydrocabon column or the cappilary effect. A new empirical equation for those two characters have been proposed in this study, which valid spesifically for South Mahakam.The equations shows maximum pressure differential is 3,500 to 4,000 psi, while the cappilary effect is in range of 240 to 270 psi which is equivalent to 230 to 275 m of gas column. Geomechanical parameter calculated at well level shows SHmax > Sv > Shmin, with the angle of SHmax is about 20 to 30° to the main fault, Sepinggan. Based on this aspects, all faults tend to dilate than to slip, showed by the value of dilatation tendency which is 0.88-0,93, compare to slip tendency 0,32-0,51. The dilatation tendency also tends to increase to distal area or Stupa’s field, along with the increase of the reservoir pressure. Syntheses of the studies give confirmation of the high sealing nature for the faults in the areas. High Vshale that have been equally distributed in vertical and lateral direction in the area, has become the main factor that control the sealing nature. Comparison of the South Mahakam data to the available literature also shows that the sealing nature can be classified as shale smear’s type. As consequence of this high Vshale, other sealing parameter is then affected either directly or not.